Republic of Ghana Diagnostic Review of Financial Consumer Protection - World Bank Group (World Bank, Washington, DC, 2017)
This diagnostic review was conducted with a purpose to inform future reform of the FCP framework in Ghana, and is based on the revised and enhanced World Bank Good Practices for Financial Consumer Protection (forthcoming). The content of this report is based on a review of the legal and regulatory framework, as well as in anecdotal evidence of current FCP issues and practices gathered through interviews with financial services providers, regulators, specialists, and through a review of available documents on this topic. The assessment focuses on retail products and services in four sectors: i) banks and NBFIs; given the large number of diverse institutions in the non-bank sector the references to NBFI sector in this report are primarily based on information gathered from rural and community banks, microfinance companies, savings and loans, credit unions, and leasing companies; ii) payments; and iii) insurance. Further, it covers five topics in each of the above-mentioned sectors, namely: i) legal, regulatory, and supervisory framework; ii) disclosure and sales practices; iii) fair treatment and business conduct; iv) data privacy; and v) dispute resolution mechanisms. While some sector-specific sections addressed issues related to data privacy, this topic was primarily addressed as cross-sectoral issue, discussed in section 2 below. Each of the sections contains recommendations for reform measures in Ghana, with indication of their priority. Significant emphasis has been put on building supervisory capacity for FCP, given its importance for effective implementation of the few existing regulations and additional regulatory reforms proposed in this report.